1976
DOI: 10.1111/j.1095-8649.1976.tb03905.x
|View full text |Cite
|
Sign up to set email alerts
|

The existence of two races of Atlantic salmon (Salmo salar L.) in the British Isles

Abstract: Sera from approximately 10 000 Atlantic salmon collected from rivers in the British Isles have been analysed. Polymorphism at the transferrin locus was observed and the distribution of the transferrin alleles provides further evidence supporting the presence of two races of salmon first postulated by Payne et al. (1971a).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
3
27
0
Order By: Relevance
“…Designation of enzymes by sub-cellular location also makes inter-specific comparison easier. Of the gene markers detected in the present study, Me m -2, Aat s -2, Sdh-1 and 2 and Idh-3 should prove most useful in population studies since at these loci the frequency of the common allele is less than 0-9, while Mdh B -3 and/or 4, Ada-2, Glo and additionally Tf (Child et al 1976) may be of more limited use because of the high frequency of the common allele. The close similarity of Idh-3 frequencies between the 1977 sample of parr and a sample of adults taken at the mouth of the River Blackwater in 1975 suggests that, at least for the ldh locus, allele frequencies are relatively constant over generations (Table 4).…”
Section: Orh 36mentioning
confidence: 91%
See 2 more Smart Citations
“…Designation of enzymes by sub-cellular location also makes inter-specific comparison easier. Of the gene markers detected in the present study, Me m -2, Aat s -2, Sdh-1 and 2 and Idh-3 should prove most useful in population studies since at these loci the frequency of the common allele is less than 0-9, while Mdh B -3 and/or 4, Ada-2, Glo and additionally Tf (Child et al 1976) may be of more limited use because of the high frequency of the common allele. The close similarity of Idh-3 frequencies between the 1977 sample of parr and a sample of adults taken at the mouth of the River Blackwater in 1975 suggests that, at least for the ldh locus, allele frequencies are relatively constant over generations (Table 4).…”
Section: Orh 36mentioning
confidence: 91%
“…Payne, Child & Forrest (1971) showed that while all Salmo salar populations examined shared a common allele (Tfj) at the transferrin locus, two alleles (Tf 3 and Tf t ) occurred only in salmon of North American origin, while another rare allele (Tf%) was specific to European salmon. Variation in the frequency of Tf 2 indicated the presence of two races of Salmo salar in the British Isles, a north-western and western Boreal race and a south-western and southern 'Celtic' race (Payne et al 1971;Child, Burnell & Wilkins, 1976). The transferrin polymorphism has also proved useful in demonstrating differences between populations of salmon from different rivers in eastern North America (MMler, 1970;Payne, 1974).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the allozyme studies of Verspoor (1986), Ståhl (1987) and Bourke et al (1997) have been brought into question by the revelation that a commonly used isoenzyme (ME-2, mMEP-2*) is likely to be acting under selection pressures (Verspoor and Jordan, 1989;Bourke et al, 1997) and as such is not a suitable marker for phylogeographic studies. This may also be the case for transferrin (Verspoor and Jordan, 1989) as used by Payne et al (1971) and Child et al (1976) in the initial investigations.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly marked for France and England-a maximum of five samples from across the region were included in studies by Bourke et al (1997) and Verspoor et al (1999). In the only studies to focus directly on this region, Payne et al (1971) and Child et al (1976) described two lineages based on polymorphisms at the transferrin locus. The so-called 'Boreal' lineage radiated from a glacial lake in the southern North Sea and was proposed to occupy most of northern Europe, including the Baltic, while the 'Celtic' race was confined to the southwest of England (UKSouthwest).…”
Section: Introductionmentioning
confidence: 99%